EFEKTIVITAS MODEL PEMBELAJARAN OPEN ENDED TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS III MIN 6 LAMPUNG UTARA - Rahma Yulianingsih; Ida Fiteriani; Rahma Diani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted to address the low critical thinking skills of third-grade students at MIN 6 Lampung Utara in learning arithmetic operations with whole numbers. Many students experience difficulties in mathematics because the learning process is still teacher-centered and focuses only on memorizing formulas without encouraging critical thinking. Finding out how well the open-ended learning approach helps students develop their critical thinking abilities is the aim of this study. This study used a posttest-only control design using a quantitative, quasi-experimental methodology. The population consisted of 79 students of grade III, while the sample was taken through cluster sampling, namely class III A as the control group and class III C as the experimental group. Data were collected using an essay test consisting of ten questions that measured critical thinking skills. The analysis was carried out using normality and homogeneity tests as prerequisites, followed by an independent sample t-test with SPSS version 26. The results showed that the data were normally distributed and homogeneous. The mean posttest score of the experimental class was 85.19, higher than the control class with 80.83. A significant difference between the two groups was indicated by the t-test's significance value of 0.003 (<0.05). In comparison to the discovery learning model, it can be said that the open-ended learning approach is more successful at developing students' critical thinking abilities. This implies that the use of learning models that involve students actively in problem-solving can improve learning outcomes and foster higher-order thinking skills in elementary school mathematics.